2014
DOI: 10.1371/journal.pone.0108375
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Staging Classification of Retropharyngeal Lymph Node Metastasis in Nasopharyngeal Carcinoma Patients Treated with Intensity-modulated Radiotherapy

Abstract: BackgroundThe development of intensity-modulated radiotherapy (IMRT) has revolutionized the management of nasopharyngeal carcinoma (NPC). The purpose of this study was to evaluate the prognostic value and classification of TNM stage system for retropharyngeal lymph node (RLN) metastasis in NPC in the IMRT era.Material and MethodsWe retrospectively reviewed data from 749 patients with biopsy-proven, non-metastatic NPC. All patients received IMRT as the primary treatment. Chemotherapy was administered to 86.2% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 27 publications
6
41
2
Order By: Relevance
“…It is possible that LN metastasis correlates better with distant metastasis-free survival (DMFS). [30,31] Since the data included in our analysis did not contain DMFS values, this hypothesis has to be verified with further studies. Hung et al [34] suggested that the SUVmax of the LNs in the neck region is an independent prognostic factor for DMFS in NPC patients treated with intensity-modulated radiation therapy (IMRT).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is possible that LN metastasis correlates better with distant metastasis-free survival (DMFS). [30,31] Since the data included in our analysis did not contain DMFS values, this hypothesis has to be verified with further studies. Hung et al [34] suggested that the SUVmax of the LNs in the neck region is an independent prognostic factor for DMFS in NPC patients treated with intensity-modulated radiation therapy (IMRT).…”
Section: Discussionmentioning
confidence: 98%
“…Patients with primary tumors characterized by a high SUV value before treatment have been demonstrated to have poor survival rates in cases of head and neck squamous cell carcinoma, lung cancer, esophageal cancer, and cervical cancer. [17][18][19]30] Another study involving meta-analysis of HNC patient data concluded that primary tumors with a high MTV or TLG before treatment are associated with worse patient survival rates. [12] The use of SUV, MTV, and TLG parameters for predicting disease prognosis is worthy of systematic evaluation in both HNC and head and neck squamous cell carcinoma (HNSCC), based on studies cited above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it occurs much more frequently in Southeast Asia and China. In Southern China, NPC is one of the most common malignant tumors and the incidence of NPC is approximately 30-80 per 100,000 per year [3]. Because of the special lesion location, nasopharyngeal carcinoma is not suitable for surgical treatment and radiotherapy play a crucial part in NPC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, it exists much more frequently in Southeast Asia and China. In Southern China, NPC is one of the most common malignant tumor and the incidence of NPC is approximately 30-80 per 100,000 per year [1]. Because of the special lesion location, nasopharyngeal carcinoma is not suitable for surgical treatment and radiotherapy plays a crucial part in NPC therapy.…”
Section: Introductionmentioning
confidence: 99%